Outcome in biopsy-proven Lupus nephritis: Evaluation of biopsies from the Norwegian Kidney Biopsy Registry. (July 2017) - Norby, G E; Mjøen, G; Bjørneklett, R; Vikse, B E; Holdaas, H; Svarstad, E; Aasarød, K
Objective: To evaluate long-term mortality and end-stage renal disease (ESRD) in a cohort of Norwegian patients with biopsy-proven lupus nephritis (LN). Methods: Renal biopsies were obtained from 178 patients with LN from 1988 until 2007. Mortality rate and death causes were provided by Statistics Norway and ESRD data were provided by the Norwegian Renal Registry. Risk factors for all-cause mortality were evaluated by Cox regression. Standardized mortality ratio (SMR) was compared to observed deaths in a matched general population sample. Results: Mean age was 37.6 (±14.4) years, and median time of follow-up was 8.5 years (0–26.2). Thirty-six patients (20.2%) died during follow-up. The SMR for all-cause mortality was 5.6 (Confidence interval [CI] 3.7–7.5). In an adjusted multivariate analysis proliferative glomerulonephritis (LN class IV) was independently associated with all-cause mortality; hazard ratio (HR) 2.6 (Confidence interval [CI] 1.2–5.7 p = 0.017). Main causes of death were infections (47.2%) and cardiovascular events 8 (22.2%). Thirty-six patients (20.2%) reached ESRD. Conclusions: Biopsy-proven LN is associated with increased mortality compared to the general population. LN class IV is associated with all-cause mortality. Infections and cardiovascular events were the most common causes of death. Patients with LN have a high incidence of ESRD.